Analisis Keterkaitan Instrumen Kebijakan Moneter, Kebijakan Defisit Anggaran dan Neraca Transaksi Berjalan Indonesia 2006q1-2016q4 - Annisaa Syifa’ Maulina; Banatul Hayati (Universitas Diponegoro, 2020)
This study analyze the linkages of monetary policy instruments BI rate ,money supply, real effective exchange rate and budget deficit as a determinant of Indonesia's current account balance periode 2006Q1 to 2016Q4. Using VAR/VECM analysis method. The results of the study show that real exchange rate and budget deficit significantly influence current account balance. Impulse response analysis shows that response of current account tends to be positive over the shock of money supply, while the shock of budget deficit, real exchange rate, BI rate and current account balance itself are responded negatively. The shock that occurred in current account is partly contributed by current account, real effective exchange rate, money supply, budget deficit and BI rate. So, to maintain the stability of the current account balance in Indonesia one of them can be controlled by monetary policy instruments ; real exchange rate, money supply, BI rate and budget deficit.